The stand for the investigation of the auditory danger signals perception – preliminary investigation - KOTARBIŃSKA, E.; MAKAREWICZ, G.; OGŁAZA, R.; PALUCHOWSKI, R.; ROGOWSKI, P. (Archives of Acoustics, 1996)
This article presents a stand for the investigation of the perception of auditory danger signals which are masked by simulating industrial noise. The test stand enables the generation of signals with specified parameters and the control of the course of an experiment. It also enables the processing of measuring data obtained. In the latter part of the paper, psychoacoustic experiments are described. Some results of preliminary measurements are discussed.